Crystal Plasticity Modeling to Capture Microstructural Variations in Cold-Sprayed Materials - Aulora Williams; YubRaj Paudel; Shiraz Mujahid; Marc Pepi; Peter Czech; Haitham El Kadiri; Hongjoo Rhee (Crystals, 2024)
The high-velocity impact of powder particles in cold-spray additively manufactured (CSAM) parts creates intersplat boundaries with regions of high dislocation densities and sub-grain structures. Upon microstructure and mechanical characterization, CSAM Aluminum 6061 showed non-uniformity with spatial variation in the microstructure and mechanical properties, affecting the overall response of the additively manufactured parts. Post-processing treatments are conducted in as-printed samples to improve particle bonding, relieve residual stresses, and improve mechanical properties. In this work, we attempt to implement the effects of grain size and distribution of smaller grains along the intersplat boundaries using the grain size distribution function and powder size information to accurately predict the deformation response of cold-sprayed material using a mean-field viscoplastic self-consistent (VPSC) model. The incorporation of an intersplat boundary term in the VPSC model resulted in a stress–strain response closely matching the experimental findings, preventing the superficially high stresses observed due to Hall–Petch effects from ultra-fine-grain structures. Likewise, the results from the grain analysis showed the combined effects of grain size, orientation, and intersplat mechanisms that captured the stresses experienced and strain accommodated by individual grains.